Levels, accumulation patterns and retrospective trends of perfluoroalkyl acids (PFAAs) in terrestrial ecosystems over the last three decades. (March 2019) - Falk, Sandy; Stahl, Thorsten; Fliedner, Annette; Rüdel, Heinz; Tarricone, Kathrin; Brunn, Hubertus; Koschorreck, Jan
Abstract: As a result of their ubiquitous presence in the environment perfluoroalkyl acids (PFAAs) have been demonstrated in numerous organisms worldwide, in particular in those of higher trophic levels. The fact that PFAAs have been detected in various human matrices, together with the resultant potential human health risks, knowledge of possible paths of entry and distribution in various ecosystems, is of great importance. In this context pooled samples of terrestrial ecosystems – roe deer liver (n = 141), earthworms (n = 44) as well as leaves from beech and poplar trees (n = 70) – from the year 1989–2015 were obtained from the German Environmental Specimen Bank and examined for the presence of 11 PFAAs for the first time. In addition to determining individual and total PFAA concentrations, temporal trends have been deduced in order to determine the effectiveness of regulatory measures. The highest total mean concentration of PFAAs (sum of the concentrations of the 11 analytes) were 9.9 μg/kg in the roe deer liver samples, followed by earthworm samples with a mean PFAA concentration of 3.5 μg/kg and leaves with a mean total concentration of 2.5 μg/kg. In regard to temporal trends there was a significant reduction of concentrations for perfluorooctane sulfonate, perfluorooctanoic acid, perfluorononanoic acid and perfluorodecanoic acid in roe deer liver from 2003 to 2015, an indication of the effectiveness of regulatory measures. The same is true for the perfluorooctane sulfonate concentrations in earthworms and for perfluorooctanoic acid concentrations in the leaves. In contrast, an increase in perfluorobutanoic acid concentrations was observed from 2003 to 2015 in all three matrices. In summary it must be noted that in spite of the discernible effectiveness of minimization strategies, PFAAs are still detectable in terrestrial matrices and concentrations of other PFAAs as perfluorobutanoic acid appear to be increasing. Graphical abstract: Image 1 Highlights: First time-course study on PFAAs in 3 matrices of the same terrestrial ecosystem. Roe deer liver, earthworms and leaves of 3 decades were analyzed retrospectively. Highest concentrations found in roe deer liver followed by earthworms and leaves. Regulatory minimization measures seem to be effective for PFOS and long-chain PFAAs. Meanwhile concentrations of possible substitutes like PFBA appear to be increasing. Abstract : Roe deer liver, earthworm and leaf samples of one and the same terrestrial ecosystem were analyzed on levels, accumulation patterns and retrospective trends over the last three decades.